Effect of stress on carcass and meat quality of sheep, goat and pig - SWAGAT MOHAPATRA; SANTWANA PALAI; SOUBHAGYA RANJAN PRADHAN; SHIVANI DAS; AMBIKA PRASAD KHADANGA MAHAPATRA; LIPIKA PRIYADARSINI; RITUN PATRA; NIRUPAMA DALAI (Indian Journal of Animal Sciences, 2023)
Domestic animals like sheep, goat and pig are subjected to many chronic stressful conditions regularly. The stressors include handling, transportation, cold, heat, temperament, diseases, parasites and introduction to a new group. Irrespective of the etiology, stress decreases the normal wellbeing and productivity of the animal. Farm animals attempt to deal with these stressors through behavioural and physiological adaptations aimed at restoring homeostasis. When these responses fail, common signs of persistent stress arise. As the symptoms of stress are unidentifiable by the farmers, there can be a significant deterioration in quality and quantity of meat produced. The increasing need for food due to population growth and urbanization has to be met through proper health management of farm animals. More research is needed to alleviate stress in farm animals and improve product quality and yield. This review paper aims to emphasize on stress factors in farm animals like sheep, goat and pig, and their impact on productivity and meat quality. With a greater understanding of stressors, altered physiological mechanisms, stress adaptability, it would be possible to implement methodologies for stress mitigation in farm animals.